Nursing Informatics: State of the Science - Grobe, S. J. (Yearbook of Medical Informatics, 1994)
Nursing informatics is a combination of computer science, information science and nursing science designed to support the practice and delivery of patient care. Using the informatics model of data, information and knowledge, the nature of automated systems to support clinicians in their delivery of high-quality care are described from their inception to their current state, and the importance of research to advance the state of nursing know ledge are emphasized. The evolution of clinical care systems and nursing management systems are viewed, as is the progress of the scientific work relative to nursing informatics. Milestones in the advancing state of the science are identified and the conclusion is drawn that although nursing informatics has evolved, much scientifically based work remains. Key nursing informatics resources identified in the paper support this conclusion about what remains to be accomplished.
Keywords: Nursing Informatics; Information Management; Nursing Research